Silenced Husbands: Muslim Marriage Migration and Masculinity. (October 2015) - Charsley, Katharine; Liversage, Anika
In both Denmark and Britain, legal and policy discourses have relied on a range of problems implicitly or explicitly linked to transnational marriages involving ethnic minorities in order to control and change the character of spousal immigration. These discourses often focus on the vulnerability of Muslim women, while Muslim men appear as patriarchal figures abusing their power over co-ethnic women. In this article, we use qualitative data from semi-structured interviews with Pakistanis in the United Kingdom and Turks in Denmark to explore gendered challenges for Muslim migrant husbands and demonstrate experiences inconsistent with the assumptions that underpin regulation. Attention to intersecting identities reveals weaknesses in such men's relational positions and multiple arenas in which their masculinity is problematized or denigrated. In combination, these representations function to limit such men's ability to give voice to their vulnerabilities and the challenges they face and thus to reinforce assumptions of male hegemony.